Saturday

April 19, 2014

April 19, 2014

Posted by **Penny** on Monday, July 15, 2013 at 4:20am.

- Math-Algebra -
**Steve**, Monday, July 15, 2013 at 4:42amthat would be just square root.

√(d-3e)

(x^2)^(1/4) = x^(1/2)

**Related Questions**

Math - Can you help me with this? I did this many times and got different ...

maths - hi, i would really appreciate some help on simplifying this question: -2...

Algebra - Simplify ..... 1. the square root of the cube root of 49a^2z^4 2. the ...

Calculus II - Integrate using integration by parts (integral) (5-x) e^3x u = 5-x...

math - Find the integral of:? i) ∫[(e^[-x]) / (-3e^[-3x] - 3e^[-2x])] and ...

ODE - compute the inverse laplace transform 2S^2+13S+5/(s+3)(s-1)^2 i got 3e^t+...

Math+Growth/Decay - 3e^2x = G -3e^2x = G -3e^-2x = D 1/8e^2x = G -1/8e^-2x = D ...

math - Deifferentiate: y=e^-3x+2 would the answer be -3e^-3x+2 or 3e^-3x+2

Physics - Which of the following equations describes the condition for observing...

Calculus - Partial Fractions - I've set a problem up, something like this. s^4: ...